ANDROID BASED WHEEL CHAIR CONTROL - Irfan, Sk.; Amudha (International Journal of Psychosocial Rehabilitation, 2020)
Innovations have increased day by day in that they can solve the problems that are faced by humans. The innovations are in the fields of education, medicine, research, and industries. The main innovations in medical research are to help the physically challenged people in the world. These kinds of people are forced to walk from one place to another. So to avoid the problem in this paper, they propose the button-controlled robot. It uses Bluetooth as the protocol for communication between the wheelchair and the controller. The Bluetooth is paired with the Android mobile. After getting paired, the button command is provided as the input. The input string is compared with the string present in the program. If the comparison is matched, the controller works based upon the command. The controller is connected with the driver and the DC motors. The battery is connected separately, which provides supply to the controller. This method is highly effective and more helpful to the physically challenged people.